20 LOW DISCUSSION RATES OF PREVENTATIVE HEALTH SERVICES IN INFLAMMATORY BOWEL DISEASE (IBD) PATIENTS. (7th February 2019) - Lynn, Amanda M; Al-Bawardy, Badr; Park, Sang Hyoung; Kane, Sunanda
Abstract: Inflammatory bowel disease (IBD) patients face a higher risk of infection, certain malignancies, metabolic bone disease, and mental health disorders secondary to their underlying disease and the medications employed as treatment. Despite the availability of guidelines regarding health maintenance in IBD patients 1, provision of preventative care services in this population remains disappointingly low. 2 We sought to evaluate the frequency at which preventative services were discussed with IBD patients in a tertiary referral center. We retrospectively reviewed patients presenting for consultation in our IBD clinic from July 1 st to December 31 st 2017. Of 256 IBD patients seen during that time frame, the first 150 patients were consecutively included to undergo chart review. We collected demographic data, IBD type and therapy employed during the time of their visit. Information was gathered about preventative services with a focus on what was discussed with the patient, as documented in the providers' clinic notes. Of 150 IBD patients, the mean age was 42.2 ± 16.0 years and 49.3% were male. 44.7% were referred by their local physician, traveling a median distance of 343.5 miles (IQR=171-807). There were 48.7% with Crohn's disease (CD), 44.7% with ulcerative colitis (UC), and 6.7% whose IBD was indeterminate. At the time of their visit, 43.3% were on corticosteroids, with another 42.7% and 20.7% on a biologic or immunomodulator, respectively (Table 1). Overall, vaccines were discussed with only 45.3% of patients, with pneumococcal vaccine reviewed most frequently at 42% and herpes zoster the least at 2.1% (Figure 1). Cervical cancer screening was discussed in only 15.1% of women. Skin cancer prevention was reviewed with 26%. Thirteen patients (8.7%) were active smokers, and cessation was recommended in 46.2%. Bone health was addressed in 55.4% of patients with identifiable risk factors. One third of patients reported a history depression or anxiety on their intake forms, but this was addressed in only 10% of affected patients. The frequency at which preventative services were discussed was suboptimal, consistent with prior reports suggesting IBD patients receive these services at a lower rate than the general population. 2 While knowledge gaps regarding guidelines, confusion over the gastroenterologist's role in this arena, time restraints, and logistical barriers have been cited as contributing factors, we believe that the low rate of discussion in this cohort likely also stems from the fact that this is a referral population composed of patients traveling long distances for consultation regarding already severe and complex disease courses. As part of a quality improvement initiative, we hope to implement checklists within our electronic medical record to serve as reminders and discussion aids in reviewing preventative health services with our patients.